Research on hierarchical service guarantee scheme for 5G network - Zhao SUN; Furong XU; Yantao HAN; Long ZHANG; Jinxia CHENG; Shanshan LIU; Wei DENG; Zhenping HU (Dianxin kexue)
The digital transformation process of economic society is accelerating.As the first of ＆quot;new infrastructure＆quot;, 5G will effectively enable the industry digital transformation.Facing the diverse needs of the industry in terms of network performance, operators need to provide the industry with hierarchical wireless service levels.Based on the analysis of 5G network performance requirements of industry services, the RAN-based service guarantee capability of 5G network was introduced from three aspects: data rate, delay and reliability.At the same time, based on the demands, various service guarantee technical technologies were combined and associated with network slice ID and 5QI to form a hierarchical service guarantee scheme.By matching industry service demands and network capacities, the integration and development of communication and vertical industry will be better promoted.